Functional behaviour of mixed protein-polysaccharide system - Kelly, Rachel Jane (1995)
The work described in this thesis addresses two classes of mixed biopolymer systems: (a) starches and sodium caseinate ; (b) gelling seaweed polysaccharides (x-carrageenan - both with and without locust bean gum - agar and alginate) and proteins (gelatin and blood plasma proteins). The viscosity and swelling volume of a 1% potato starch paste in distilled, deionised water is markedly reduced in the presence of caseinate. Similar effects were seen with simple electrolytes suggesting that this occurs as a consequence of a non-specific ionic strength effect. In contrast a 4% maize starch paste in distilled, deionized water undergoes a viscosity and swelling volume increase in the presence of caseinate. However, when pasted in a 0.1M, pH 7.0 phosphate buffer caseinate addition has little effect on the viscosity of the fresh paste and at high concentrations appears to prevent retrogradation on ageing. It is suggested that in buffer caseinate prevents the leaching of starch polysaccharides from the swollen granule and therefore maintains amylose in the granular phase. This is attributable to the high ionic strength of the solvent, allowing caseinate and the starch polysaccharides to phase separate. In water the unfavourable entropy, change due to the uneven distribution of the counter-ions, prevents phase separation and results in an interpenetrating network. Studies on the large deformation stress relaxation behaviour and melting points of 2% carrageenan, 0.5% carrageenan/0.5% locust bean gum (LBG) and 2% agar gels in a variety of solvent media indicate that the inclusions of 0-20% gelatin and 0-5% bovine serum albumin (BSA) give different results depending on both protein and polysaccharide. The main points of this study show that agar/gelatin mixed gel undergoes a distinct phase inversion at 4-7% gelatin levels, which is not seen with the carrageenan gels containing gelatin. Even when 20% gelatin is incorporated into a 2% carrageenan gel the melting point of the gel is unaltered from that of carrageenan alone. In the presence of high levels of BSA the carrageenan/LBG gel undergoes a marked increase in melting point. Investigations using locust bean gums of variable protein content suggests a possible (LBG)protein-BSA interaction since the melting point increases with the LBG protein content. It is shown that carrageenan/LBG gels have clear regions when formed by autoclaving in the presence of blood plasma. This supports the idea of an association between the protein in the insoluble husk and the blood plasma proteins.